Spleen Stiffness Measurement by Using Shear-Wave Elastography as a Predictor of Progression to Secondary Myelofibrosis - Ekinci, Omer; Ozgokce, Mesut; Turko, Ensar; Merter, Mustafa (Lippincott Williams & Wilkins, 2021)
Objective Polycythemia vera (PV) and essential thrombocythemia (ET) are chronic myeloproliferative diseases that can transform to secondary myelofibrosis (SMF). In this study, we evaluated spleen stiffness using shear-wave elastography (SWE) as a predictor of progression to SMF. Methods Participants were grouped as healthy volunteers (HVs), PV/ET patients, and SMF patients. Participants' spleen sizes, spleen stiffness values, bone marrow fibrosis degrees, and the other parameters were evaluated. Spleen stiffness values and spleen sizes were compared between groups. Results Of the 121 participants included in this study, 52 patients were HVs, 52 patients were PV and/or ET patients, and 17 patients were SMF patients. In terms of age and sex, there was no difference between groups. Splenic parenchymal stiffness median values by using SWE were found to be 0.82 m/s in HVs, 1.41 m/s in PV/ET patients, and 2.32 m/s in SMF patients (P < 0.001). In terms of median length of the spleen, the difference between groups was significant (P < 0.001). In addition, we found a significant positive correlation between spleen stiffness and bone marrow fibrosis degree (P < 0.001, r = 0.757). However, in multivariate analysis, there was no strong independent risk factor for spleen stiffness. Conclusion In this study, we showed that measurement of spleen stiffness using SWE can distinguish SMF from PV/ET patients and HVs. Therefore, we believe that SWE may be used as a noninvasive and easily accessible method to check the fibrotic progression of bone marrow in PV and ET patients to monitor the transformation to SMF, and enables to detect fibrosis in early phase.
Keywords: shear-wave elastography; secondary myelofibrosis; chronic myeloproliferative neoplasms